Co-encapsulation of L-ascorbic acid and quercetin by gelatin/sodium carboxymethyl cellulose coacervates using different interlayer oils. (July 2021) - Ji, Ran; Cui, Heping; Duhoranimana, Emmanuel; Hayat, Khizar; Yu, Jingyang; Hussain, Shahzad; Usman Tahir, Muhammad; Zhang, Xiaoming; Ho, Chi-Tang
Graphical abstract: Highlights: Double emulsion prior to complex coacervation was effective for co-encapsulation. Mononuclear ellipse-like shape was obtained at 2% total biopolymer concentration. Structural similarity of conjugated linoleic acid and PGPR damaged co-encapsulation. The capsules made by conjugated linoleic acid has worst encapsulation of vitamin C. Quercetin carried by conjugated linoleic acid and fish oil got better encapsulation. Abstract: A two-step emulsification prior to complex coacervation was employed to develop a co-encapsulation technology of hydrophilic and hydrophobic components for nutrition enhancement. Processing parameters of mononuclear ellipse-like microcapsules using gelatin and sodium carboxymethyl cellulose as wall materials were evaluated. The particle size and morphology of microcapsules and the encapsulation efficiency of L-ascorbic acid were significantly affected by the water–oil phase ratio and total biopolymer concentration. The L-ascorbic acid and quercetin co-encapsulated microcapsules with an average size of 65.26 µm showed good physical and chemical stability. The encapsulation efficiencies of L-ascorbic acid and quercetin were 69.91% and 88.21%, respectively. To predict the potential of functional lipids as hydrophobic carriers, microcapsules using soybean oil, olive oil, fish oil, and conjugated linoleic acid as interlayer oils were developed. The encapsulation efficiencies of hydrophobic compounds carried by different oils were similarly high (88.21–93.08%), whereas, hydrophilic ones carried by conjugated linoleic acid had the lowest encapsulation efficiency (32.54%). The interface tension results indicated that the interfacial stability was impaired by a competitive relation between conjugated linoleic acid and hydrophobic emulsifier at the interface, due to their structural similarity. These results provided the guidance for improving the quality of interlayer oils from microcapsules.